THE INFLUENCE OF THE HUMIDITY OF THE AIR ON THE CARDIOVASCULAR SYSTEM (American Journal of Interdisciplinary Research and Development, 2025)
This article will investigate the effects of different levels of humidity on the circulatory system, including blood pressure, heart rate and general cardiovascular health. As well as analyzing the relationship between air humidity and health indicators related to circulatory system function in order to develop recommendations for the prevention of cardiovascular diseases depending on climatic conditions.